(untitled) (REMUNOM, 2025)
Nephrolithiasis represents a condition of high clinical and epidemiological relevance, characterized by the formation of calculi in the urinary system, affecting 10-15% of the world population with an upward trend in recent decades. This study aimed to synthesize scientific evidence on prevalence, epidemiological profile, economic impact, and challenges of contemporary nephrolithiasis management through an integrative literature review. A systematic search was conducted in PubMed/MEDLINE, SciELO, LILACS, Web of Science, and Scopus databases, including studies published between 2000 and 2025. Observational studies, reviews with quantitative data, guidelines, and economic analyses were selected through a screening process by two independent reviewers. The narrative synthesis was structured into three thematic axes: prevalence and temporal trends, epidemiological profile, and economic burden. Results showed global prevalence of 1-19.1%, with an increase of over 150% in the United States between 1980-2016. Age distribution concentrates between 20-50 years, with a historical male:female ratio of 2-3:1, although progressively decreasing. Strong association was identified with metabolic syndrome, obesity, diabetes mellitus, and arterial hypertension. Direct costs in the United States exceed US 5 billion annually, while in Brazil the public system spent approximately R 62 million annually. Recurrence rates reach 50% in 10 years without adequate prevention. It is concluded that nephrolithiasis constitutes a growing public health problem, demanding robust preventive policies, expanded access to cost-effective treatments, and strengthening of health education strategies for modification of modifiable risk factors.